Heparin-Induced Thrombocytopenia: A Focus on Thrombosis. Issue 1 (January 2021) - Arepally, Gowthami M.; Padmanabhan, Anand
Abstract : Heparin-induced thrombocytopenia is an immune-mediated disorder caused by antibodies that recognize complexes of platelet factor 4 and heparin. Thrombosis is a central and unpredictable feature of this syndrome. Despite optimal management, disease morbidity and mortality from thrombosis remain high. The hypercoagulable state in heparin-induced thrombocytopenia is biologically distinct from other thrombophilic disorders in that clinical complications are directly attributable to circulating ultra-large immune complexes. In some individuals, ultra-large immune complexes elicit unchecked cellular procoagulant responses that culminate in thrombosis. To date, the clinical and biologic risk factors associated with thrombotic risk in heparin-induced thrombocytopenia remain elusive. This review will summarize our current understanding of thrombosis in heparin-induced thrombocytopenia with attention to its clinical features, cellular mechanisms, and its management.